3x-5(x-3)=-7+5x-34

Simple and best practice solution for 3x-5(x-3)=-7+5x-34 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-5(x-3)=-7+5x-34 equation:


Simplifying
3x + -5(x + -3) = -7 + 5x + -34

Reorder the terms:
3x + -5(-3 + x) = -7 + 5x + -34
3x + (-3 * -5 + x * -5) = -7 + 5x + -34
3x + (15 + -5x) = -7 + 5x + -34

Reorder the terms:
15 + 3x + -5x = -7 + 5x + -34

Combine like terms: 3x + -5x = -2x
15 + -2x = -7 + 5x + -34

Reorder the terms:
15 + -2x = -7 + -34 + 5x

Combine like terms: -7 + -34 = -41
15 + -2x = -41 + 5x

Solving
15 + -2x = -41 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
15 + -2x + -5x = -41 + 5x + -5x

Combine like terms: -2x + -5x = -7x
15 + -7x = -41 + 5x + -5x

Combine like terms: 5x + -5x = 0
15 + -7x = -41 + 0
15 + -7x = -41

Add '-15' to each side of the equation.
15 + -15 + -7x = -41 + -15

Combine like terms: 15 + -15 = 0
0 + -7x = -41 + -15
-7x = -41 + -15

Combine like terms: -41 + -15 = -56
-7x = -56

Divide each side by '-7'.
x = 8

Simplifying
x = 8

See similar equations:

| 9(x-13)=-13+x | | ax+box+2=-11 | | x^5-3x^4-5x^3+15x^2=0 | | 2.5+5=15 | | (5x-3)+68=90 | | -12(1-7m)+1=11m+62 | | 2(x-2)+3(5x)=39 | | -12+11-30=5-30 | | 3x+12+7x+x= | | x^3-x^2-8x-12=0 | | 46+10p=-4(14-11p) | | X+20+7x=90 | | 6x^2+36x+54=x | | f(x)=-4+2x^2-x | | 5x-10=240 | | ln(x-6)-ln(x+6)=2 | | x^(3/2)=9/8 | | 2(2w-4)+2w=64 | | 6x^2+6x+54=x | | x^3/2=9/8 | | 18xn=18 | | 5x+32=0 | | 4c=w | | (-2x)+5+3x-4x+(-1)+(-x)=4(4x) | | -13x-43=7(x-13)+4x | | 5(2x-6)=-3 | | -10(2x-6)-6(10+3x)=8x+6x | | 0.4x=0.1(x-100)-70 | | (x-3)(x+3)+15=8x | | ((x^2)/6)-(2)=0 | | 7x-9+5x=6x-3 | | 7[1-(-8x-9)]=224x+259 |

Equations solver categories